Judges’ disciplinary liability for apparent and flagrant contempt of provisions of law versus principle of judicial independence (Ius Novum, 2019)
The article aims to present the issue of the limits of a judge’s disciplinary liability for a company-related misdeed in the form of apparent and flagrant contempt of the provisions of law limited by the principle of judicial independence. Due to the fact that the principle of statutory determination of an act is not applicable in disciplinary law, the sphere is shaped by disciplinary case law, in particular by the judgments of the Supreme Court-Disciplinary Court, which are thoroughly analysed. This makes it possible to indicate tendencies occurring in case law and develop the author’s own stance taking into account the latest amendments to the Act: Law on the common courts system, which can be translated into the need to increase the protection of judicial independence and a more restrictive approach to the use of the instrument of disciplinary liability towards judges who commit apparent and flagrant contempt of the provisions of law in the sphere of adjudication.
Keywords: disciplinary liability; judicial independence; company-related misdeed; apparent and flagrant contempt of the provisions of law; disciplinary courts